Ipomoea Reniformis: Isolation, Characterization, and Evaluation of Scopoletin and its Antioxidant and Cytotoxic Activities - Manapure, Sharad R.; Sawale, Jyotiram A.; Ittadwar, Abhay M. (International Journal of Membrane Science and Technology, 2023)
The Ipomoea reniformis is found predominantly all over India and is used traditionally for several diseases including for the cure of cancer. This study aimed to isolate and characterize phytoconstituents from bioactive extract, evaluate antioxidant and cytotoxic properties of chloroform (CH), ethyl acetate (EA), ethanol (ET), hydroalcoholic (HA) (50%v/v) extracts and isolated compound. Antioxidant property was evaluated by using 1,1-Dipheny l, 2-picryl hydrazyl (DPPH) radical scavenging assay and cytotoxic potential was evaluated by using MTT (3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide) Assay. All the extracts (CH, EA, ET, HA) of Ipomoea reniformis exhibited significant antioxidant potential but the highest antioxidant activity (94.84 ± 1.56 % at 1000 µg/ml) was shown by ET extract with IC50 value of 52.24 µg/ml and SM (scopoletin) isolated from ET extract showed more potent antioxidant activity IC50 value of 52.24± 0.9367 µg/ml, and the highest antioxidant activity (96.29± 0.86 %) at 1000 µg/ml compared to ET extract. The percent cell viability of MCF-7, A-549, and HCT-116 human cell lines was evaluated by treatment with CH, EA, ET, HA extracts and SM. The percent cell viability was found to be, ET (4.4117 ± 6.2711%, 0.0605 ± 0.7748%, 9.8290 ± 2.1149%) and SM (4.23± 1.38%, 0.059 ± 0.32 %, 8.92 ± 0.87%) for MCF-7, A-549, HCT-116 respectively. Therefore, from the present study it was concluded that isolated SM has more potent antioxidant and cytotoxic potential than ET extract of Ipomoea reniformis.